Surveillance strategy of Barrett's esophagus in the Asian region with particular reference to its locoregional epidemiology. Issue 4 (12th May 2020) - Di, Jia; Sharma, Neel; Pérez, Lady K M; Zhang, Jun; Ho, Khek‐Yu
Abstract: Barrett's esophagus (BE) is a premalignant condition associated with the development of esophageal adenocarcinoma (EAC). Over the past decade, BE and its associated neoplasia has increased in prevalence globally. Current surveillance guidelines aimed to detect and treat BE‐associated dysplasia early in the hope of improving the morbidity and mortality of the condition. However, due to the lack of long‐term data and the proven benefit that surveillance actually improves mortality from EAC, the guidelines of the United States and Europe are slightly different. This review will focus on discussing the surveillance strategy for BE appropriate for the Asian region, taking into account the unique epidemiologic features of this disease in the Asian region. Abstract : Current surveillance guidelines aim to detect Barrett's esophagus‐associated dysplasia early. However, due to the lack of long‐term data, and proven benefit that surveillance actually improves mortality from esophageal adenocarcinoma, the guidelines coming from the US and Europe are slightly different. This review will discuss the surveillance strategy for Barrett's esophagus appropriate to the Asian region, taking into account the unique epidemiologic features of this disease in the Asian region.